Optimization of Proteins Recovery Process from Cheese Whey - Cuellas, Anahí (2015)
The process to obtain a protein-containing ingredient from the remaining whey of Argentinean “Cuatriolo” cheese production was studied. In order to optimize the protein recovery, physical and chemical treatments were investigated. Two protocols with different sequences of application of heating step and acid addition were assayed in the presence and absence of fat and CaCl2. The results were evaluated by the yield, water retention and particle size. The results showed that the highest yield of the process (76.6%) and an increase in water retention (39.8 w/w) were achieved when the acid was added after boiled and incubated for 30 min at 90 °C. In these working conditions, the presence of calcium shows a lower yield of recovery (72.8%) and this behaviour correlates with a smaller particle size. Additionally, the presence of fat reduces the particle size and decreases the performance of the process (69.4%). Thus, the yield of protein recovery is related to the particle size of the aggregates, i.e., the recovery of proteins increases when increase the particle size. The simultaneous presence of fat and CaCl2 increases the amount of water retained in the aggregated protein (47.62 w/w). In conclusion, the process of aggregation in whey protein should take into account both the design of suitable protocol and the presence of fat and additives.